THE STUDENTS’ ABILITY IN TRANSLATING ENGLISH IDIOM - Paranoan, Emon (DINAMIS, 2021)
The tittle of local research is The Students’ Ability In Translating English Idiom which researching the student of English letters students and graduate student in Titip Sentani Courses . The main problem of this research is to see the quality of translation English idiom result that done by fifth semester students of English letter in USTJ and Titip students course. The purpose of this study is to see whether both fifth semester of English letters and Titip students able to translate English idiom expressions of the source language to the target language (English to Indonesian), and whether students used many translation types in their translation. The method is used to take the data collection of this study are giving a set of test and questioners to the students. By using both of those procedures above, the data can be known and also students result that have translated, were analyzed to see that how far are the fifth semester students and Titip students able to transfer the core meaning of the source language to target language. There are many problems faced by students in translation process that is, students in fifth semester of English letters and Titip students found difficult words and the new idiom meaning to construct the sentence into the target language. The result of this local research show that students in fifth semester and Titip graduate students used free translation, word for word translation and literal translation types in their translation. The better translation result in translation done by a big part students of Titip students course that be able to transfer the idiom from the source language into the target language which is Bahasa Indonesia by using their existing language knowledge of both these language.